(1179) evaluation of investment efficiency in Czechoslovakia تقييم كفاءة الاستثمار في تشيكوسلوفاكيا - srein, zdenek (the institute of national planning, 2018)
evaluation of investment projects is one of the essential elements of investment planning. criteria and methodology applied significantly influence the decision-making of all the institutions involved in investment activity:firms, industrial unions, financing banks.